Estella’s Formation of Identity in Cruella (2021) Movie: A Psychological Theory - Nissa Ratna Mawarti; Syahara Dina Amalia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The aims of this qualitative study are to identify Estella’s identity formation using and to figure out factors that influence Estella’s formation of identity using psychological theory. The main character’s identity formation scrutinized in the movie adopted Marcia's theory of identity status which comprises four phases such as identity diffusion, foreclosure, moratorium, and achievement. Data collection was carried out by watching the movie many times, reading several related articles, noting important elements, and categorizing the data based on Marcia’s theory. In analyzing the data, the researchers borrowed Miles, Hubermans, and Saldana (2019) technique of analyzing data. The researchers found that Estella Miller's life before turning into Cruella De Vil was the same as a normal child's life. However, her identity began to change when she found out the mastermind behind her late mother's death. Lastly, the reason Estella turned into Cruella was because she wanted revenge on Baroness and the factors of losing her mother, social environment, ambition, and creativity within her. Based on the results of this study, researchers acknowledge that the formation of Estella's identity based on Marcia's status identity theory is mostly at the moratorium stage and the factors that influence the formation of Estella's identity are internal and external factors